A Prevalence Anatomic-Imaging Study of the Posterior Inferior Cerebellar Artery’s Origin - Ana-Maria Davidoiu; Mugurel Constantin Rusu; Corneliu Toader; Petrinel Mugurel Rădoi (Medicina)
Background and Objectives: Typically, the vertebral arteries (VAs) enter the posterior fossa through dural rings and further unite, forming the basilar artery. The posterior inferior cerebellar artery (PICA) is usually a branch of the V4 segment of the VA (intradural origin). It may also leave the V3 suboccipital segment of the VA (extradural origin). The transdural origin of the PICA within the VA’s dural ring has been consistently overlooked. A study was designed to determine the topographical patterns of the PICA’s origin. Materials and Methods: Determinations were performed in a retrospective sample of 225 computed tomography angiograms. Four types of PICA origin were documented: type 0, absent PICA; type 1, the extradural origin of the PICA from the V3 segment of the VA; type 2, the transdural origin of the PICA within the dural ring; and type 3, the intradural origin of the PICA from the V4 segment of the VA. The bilateral symmetry of types was also investigated. Results: Out of 450 VAs, type 0 (absent PICA) was found in 36%, type 1 (extradural) in 0.44%, type 2 (transdural) in 5.56%, and typical type 3 in just 58%. In types 1 and 2, the PICA entered the posterior fossa through the dural ring and the marginal sinus. In the overall group (N = 225), the type combinations 1_1, 1_2 and 1_3 were not found. Bilaterally absent PICAs occurred in 18.67%. The bilateral combinations 0_1/0_2/0_3/2_2/2_3/3_3 were found, respectively, in 0.89%/3.11%/30.67%/1.78%/4.44%/40.44%. Four of the seventy-eight PICAs opposite to an absent one, three intradural and one transdural, were true bihemispheric PICAs. Conclusions: The PICAs with extradural or transdural origins are facultative contents of the dural ring and are at risk during neurosurgical approaches in the foramen magnum. Rare bihemispheric PICAs could originate either intradurally or within the dural ring.